2018
DOI: 10.1038/s41379-018-0081-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of metaplastic breast carcinomas reveals genetic heterogeneity and relationship to ductal carcinoma

Abstract: Metaplastic breast carcinomas comprise a histologically heterogenous group of tumors. Although most are triple (estrogen/progesterone receptor, HER2) negative, these rare tumors are clinicopathologically distinct from other triple negative carcinomas and may be aggressive with worse chemotherapy responses. On the other hand, metaplastic carcinomas are histologically diverse, which is reflected in gene expression differences among subtypes. Whether metaplastic carcinomas are genetically distinct from other trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 74 publications
5
72
0
Order By: Relevance
“…Broadly, our sequencing data recapitulate those of recent studies [7,10,36,37]. An inverse correlation between PI3KCA mutations and the chondroid phenotype has been documented [7,37], and while two out of ten PI3KCA-mutated cases showed chondroid differentiation, none of the cases were purely chondroid, nor were they specifically enriched. We also presented evidence for a significant enrichment of co-occurring mutations in TP53, PTEN, and PIK3CA in MBC, a novel finding that counters the long-held concepts that TP53 and PTEN [38], and PIK3CA and PTEN [39] mutations are mutually exclusive.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Broadly, our sequencing data recapitulate those of recent studies [7,10,36,37]. An inverse correlation between PI3KCA mutations and the chondroid phenotype has been documented [7,37], and while two out of ten PI3KCA-mutated cases showed chondroid differentiation, none of the cases were purely chondroid, nor were they specifically enriched. We also presented evidence for a significant enrichment of co-occurring mutations in TP53, PTEN, and PIK3CA in MBC, a novel finding that counters the long-held concepts that TP53 and PTEN [38], and PIK3CA and PTEN [39] mutations are mutually exclusive.…”
Section: Discussionsupporting
confidence: 87%
“…Our exome sequencing data highlight the relative paucity of mutations across these MBC cases and confirm the high frequency of TP53 mutation . Broadly, our sequencing data recapitulate those of recent studies . An inverse correlation between PI3KCA mutations and the chondroid phenotype has been documented , and while two out of ten PI3KCA‐ mutated cases showed chondroid differentiation, none of the cases were purely chondroid, nor were they specifically enriched.…”
Section: Discussionsupporting
confidence: 87%
“…They are, however, frequently mutated in several other types of cancers and represent one of the most frequently observed mutations after TP53 gene mutation. Interestingly, TP53 mutations seem to be less common in spindle cell MBCs or other low-grade MBCs compared to matrix-producing or high-grade MBC subtypes [19]. This is well in line with our case, as we found two PIK3R1 and a TERT-promotor mutation but no TP53 mutations.…”
Section: Discussionsupporting
confidence: 91%
“…From a molecular point of view, mutations in PIK3CA, PIK3R1 and PTEN genes are significantly more frequently found in MBC as compared to triple-negative breast carcinomas of no special type [17]. TERT-promotor mutations are relatively more frequently associated to MBC with spindle cell morphology as compared to other types of MBCs [18,19]. They are, however, frequently mutated in several other types of cancers and represent one of the most frequently observed mutations after TP53 gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…25 This was also evident in a recent sequencing study of 28 metaplastic carcinomas including different histologic variants. 30 Interestingly, this study showed that telomerase reverse transcriptase (TERT) promoter mutations vary among subtypes, as they are common in spindle cell carcinoma and SCC (47% of tumors) but are absent in metaplastic carcinomas with chondroid mesenchymal differentiation. Taken together, these studies suggest that metaplastic carcinomas are distinct from TNBCs, and that specific histologic variants of metaplastic carcinoma have both common and unique genetic defects, which needs to be further investigated.…”
Section: Metaplastic Breast Carcinomas Harbor Genementioning
confidence: 94%